DEVELOPMENT, OPTIMIZATION AND IN VITRO CHARACTERIZATION OF HALOPERIDOL NANOCRYSTALS USING 32 FACTORIAL DESIGN - SARITHA, DAMINENI; CHANDRA BOSE, P. SUBHASH; OSMANI, RIYAZ ALI M.; IRIVENTI, PADMINI; KANNA, SANDEEP; RAVI, GUNDAWAR (International Journal of Applied Pharmaceutics, 2024)
Objective: The main aim of the present study was to improve the dissolution rate of Haloperidol nanocrystals and thereby increase their bioavailability. Haloperidol is a typical antipsychotic drug and it is used to treat schizophrenia as well as acute mania and mixed states associated with bipolar disorder. Haloperidol falls into the Biopharmaceutics Classification System (BCS-II) class of drugs (poorly soluble aqueous and highly permeable) and has poor bioavailability. Methods: The present study involves the preparation and optimization of Haloperidol nanocrystals by the anti-solvent precipitation method using Polaxomer407 and polyvinyl pyrrolidone K30 (PVP K30). The prepared nanocrystals were evaluated for various parameters like particle size, zeta potential, % drug content, % yield, surface morphology, drug-excipient compatibility studies (Fourier-transform infrared spectroscopy (FT-IR) and Differential Scanning Calorimetry (DSC)), and in vitro dissolution studies. Results: Nine preparations were done and the best preparation amongst them was selected for further studies. F7 preparation containingpolaxomer407 and PVP K30 was selected as optimized preparation based on their evaluation parameters. 32 factorial design was used in the preparation. The particle size of the F7 nanocrystals was 300.2±2.7 nm and the zeta potential-36.3±3.2 mV. The % yield was in the range of 63.62±0.3%-98.21±0.8 %. The drug content of various preparations was found to be in the range of 58.46±0.8%-93.54±0.5 %. In vitro dissolution studies showed the highest % drug release for F7(91.54±0.03%) in 10 h. Conclusion: F7 preparation was found to be having acceptable characteristics and thus selected as optimized preparation.